Phase transformations during continuous cooling of polycrystalline β-CuAlBe alloys - Montecinos Espinoza, Susana de Los Angeles (2009)
The transformations during continuous cooling and their effect on the thermoelastic behaviour of β-CuAlBe shape memory alloys have been studied by electrical resistometry, microscopy and differential calorimetry. Under slow cooling rates, the alloys show hypereutectoid behaviour as a result of the addition of Be. The sequence of γ 2 and α′ precipitation and the ordering of β phase were clearly identified. A quasi-binary phase diagram with variable Be content is proposed. Small modifications in the Be content cause noticeable changes in the ranges of phase stability. The precipitation could be avoided with high cooling rates. The precipitation processes produce changes in the matrix composition, which affect the critical temperatures of ordering as well as the β-martensite transformation. © 2007 Elsevier B.V. All rights reserved.